PECTIN FERMENTING COLIFORM BACTERIAI INCIDENCE IN WATER - SANCHEZ MARROQUIN, AY; FARRERA, BERTA (Instituto de Salubridad y Enfermedades Tropicales, CD MEXICO, DF, MEX, 1948)
Very few specimens of this peculiar "axolotl" of Lake Patzcuaro, Mex, are known The present article reports on a specimen found in the Alfredo Duges Mus Nat Hist of the Univ Guanajuato, Guanajuato, Mex, in an excellent state of preservation, with a
REV SOC MEX HIST NAT
Keywords: PECTINFERMENTING COLIFORM, BACTERIA I INCIDENCE, WATER; CIENCIAS DE LA VIDA